RESPONSE VISITOR’S TO PRODUCT DESIGN SOUVENIR IN THE BONO TOURISM AREA OF TELUK MERANTI DISTRICT - Zulita "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the visitor's response to Product design Souvenir in the Bono Tourism Area of Teluk Meranti District. This research uses descriptive quantitative research method. There are 50 samples taken by accidental sampling. Data collection techniques in this study used observation, interviews, questionnaires and documentation. Likert scale is used to measure intervals in quantitative data. This research uses Sugiyono's Theory. The results of the study show that the Visitor Response to Souvenirs in the Bono Attractions area is included in the Very Good category.